2003
DOI: 10.1302/0301-620x.85b7.13782
|View full text |Cite
|
Sign up to set email alerts
|

Prospective clinical study of autologous chondrocyte implantation and correlation with MRI at three and 12 months

Abstract: In order to determine the usefulness of MRI in assessing autologous chondrocyte implantation (ACI) the first 57 patients (81 chondral lesions) with a 12-month review were evaluated clinically and with specialised MRI at three and 12 months. Improvement 12 months after operation was found subjectively (37.6 to 51.9) and in knee function levels (from 85% International Cartilage Repair Society (ICRS) III/IV to 61% I/II). The International Knee Documentation Committee (IKDC) scores showed an initial deterioration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
154
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(165 citation statements)
references
References 16 publications
6
154
0
5
Order By: Relevance
“…Different trials give different results for the proportion who get hyaline after ACI, with higher proportions in the trial by Bentley and colleagues 64 and in the case series reported by Henderson and colleagues 75 than in the trial by Horas and colleagues. 65 If one assumes that hyaline cartilage is the desired outcome, on the basis that hyaline cartilage can last for life (most people do not need knee replacements in their lifetime), then ACI becomes the best option (in clinical effectiveness terms) because it gives the highest chance of the defect being filled with hyaline cartilage.…”
Section: Issues With Evidence For Clinical Effectivenessmentioning
confidence: 98%
See 1 more Smart Citation
“…Different trials give different results for the proportion who get hyaline after ACI, with higher proportions in the trial by Bentley and colleagues 64 and in the case series reported by Henderson and colleagues 75 than in the trial by Horas and colleagues. 65 If one assumes that hyaline cartilage is the desired outcome, on the basis that hyaline cartilage can last for life (most people do not need knee replacements in their lifetime), then ACI becomes the best option (in clinical effectiveness terms) because it gives the highest chance of the defect being filled with hyaline cartilage.…”
Section: Issues With Evidence For Clinical Effectivenessmentioning
confidence: 98%
“…In a series of 135 patients from Melbourne treated with ACI, 22 required further surgery, in most cases due to problems with the periosteal cap. 75 Since the intention is always the same -to repair the damaged area with hyaline cartilage -the end result may be the same, but costs may differ.…”
Section: Issues With Evidence For Clinical Effectivenessmentioning
confidence: 99%
“…In brief, autologous chondrocytes are harvested by arthroscopy from a lesser weight-bearing area of the joint, expanded in monolayer culture and re-implanted into the damaged area under a natural or synthetic membrane by an open joint surgical procedure (Brittberg et al, 1994). Robert Jones & Agnes Hunt (RJAH) Hospital, Oswestry and others report a high percentage of good to excellent clinical results (Bhosale et al, 2009;Henderson et al, 2003). Although there is limited long-term follow-up data, especially from the modern methods of ACI, positive clinical results are beginning to emerge.…”
Section: Introductionmentioning
confidence: 99%
“…MRI imaging was performed on a 7.1 T horizontal-bore instrument (Oxford Magnet, Oxfordshire, United Kingdom) to acquire 2D coronal images of the goat knee joints (256 × 256 matrix size, 6 × 6 cm FOV, 1.5 mm slice thickness, TR = 500 ms, TE = minimum, flip angle = 60°, eight averages). Images were graded by three blinded readers according to a scale with features of signal, defect fill, and bone edema (adapted from Henderson et al 36 ) as well as features of surface integrity and contour and cartilage thickness (adapted from Marlovits et al 37 ). The scale was adapted to allow for representation of features from both of the referenced grading schemes used previously, and a four-category ranking was used for each feature for consistency across schemes (0–3, 3 = nondegenerate cartilage).…”
Section: Methodsmentioning
confidence: 99%